Relation between Helicobacter pylori and nausea and vomiting in pregnant women - Dolatian, M; Zojaji, R; Alavi- Majd, H (Advances in Nursing & Midwifery, 2009)
Abstract Background: Gestational nausea and vomiting in pregnant women have a high prevalence. The disorder will usually be better after the third trimester but, in some cases, it persists throughout pregnancy and makes the life of pregnant women disturbed. Purpose: This case-control retrospective study was conducted to determine the relation between Helicobacter pylori and nausea as well as vomiting in pregnant women referring to the healthcare centers affiliated to Mashhad University of Medical Sciences in 2006. Methods: 187 pregnant women at the third trimester of their pregnancy were selected. According to the experience of nausea and vomiting from the first trimester, they were divided into two groups: 89 women with the disorder and 98 women without it. A questionnaire in three parts was used for data collection: demographic information, history of nausea and vomiting, and socioeconomic status.The questionnaire was validated by context validity and reliability by test-retest method.Anti-Hp immunolobin G (IgG) serum antibody wastested by ELISA ti determine seropositivity. (r=0/89) Results: The result showed a significant relation between helicobacter pylori and nausea and vomiting during pregnancy. The subjects did not have significant differences in terms of height, job, education of spouse, husbands’ job, pregnancy and BMI except for age and socioeconomic status (P=0.037 and P<0.001respectively). Conclusion: The results may show that nausea and vomiting during pregnancy can be prevented by diagnosing helicobacter pylori infection in women. Also, it seems that there should be a training program in knowing Helicobacter pylori infection and its complications. Considering the results of this research, studying women with nausea and vomiting during pregnancy for helicobacter pylori infection is advisable. Key words: Nausea, Vomiting, Helicobacter infection, Pregnancy.